A Survey on Assessing the Knowledge, Attitude and Behavior of Community Pharmacists to Adverse Drug Reaction Related Aspects - BJ, Mahendra Kumar; A, Sandeep; M, Soumya (Indian Journal of Pharmacy Practice)
Many hospitalizations in India are due to Adverse Drug Reactions (ADR) and resulting in morbidity and mortality in majority cases in addition to the huge economic burden. Asurvey was conducted to assess the knowledge, attitude and behavior of community pharmacists towards ADR related aspects. One hundred and twenty eight pharmacists from various community pharmacies in two districts of South India were consented in this survey. Aquestionnaire was prepared to investigate the knowledge, attitude and behavior of pharmacists regarding ADR reporting and distributed to the identified pharmacies. The data was collected and analyzed by ANOVA and t-test. Out of 342 community pharmacies approached, 128 (37.4%) community pharmacists consented to be part of the survey and the questionnaire given was filled and returned by them. Out of these respondents, only 39 (30.5%) pharmacists had knowledge about ADRs, 15 (11.7%) and 14 (10.9%) were aware of National Pharmacovigilance Program (NPP) and regional reporting centers respectively. Only 54 (43%) agreed that ADR reporting is a professional responsibility of pharmacists and none of the respondents reported ADRs. The main reason for not reporting any ADR was 'they did not know how to report' and 'did not feel its beneficial'. This survey revealed that the community pharmacists were having least scores towards knowledge, attitude and behavior on ADRs in Indian Scenario.
Keywords: ADRs; National Pharmacovigilance Centre; Pharmacovigilance; Community Pharmacist